Mercury enrichment in anthrosols and adjacent coastal sediments at a Classic Maya site, Marco Gonzalez, Belize. Issue 6 (1st July 2021) - Turner, Simon; Graham, Elizabeth; Macphail, Richard; Duncan, Lindsay; Rose, Neil L.; Yang, Handong; Whittet, Richard; Rosique‐Esplugas, Cristina
Abstract: Elevated concentrations of total mercury (THg) are found in the surface soils and flanking wetland sediments at the Classic Maya coastal site of Marco Gonzalez, Belize. Significant concentrations (up to 1.3 µg·g −1 dry mass) of THg occur in leaf litter‐rich soils, as well as in the artefact‐rich anthrosol spread over the vegetated mound site of structures and occupation debris. The abundance and spatial pattern of major and trace elements measured in the surface soils indicate both site‐scale controlling factors of topography, structures and vegetation on soil geochemistry as well as local highs in concentration compared with background, due to human activity. Geochemical stratigraphy of wetland sediment cores shows that a shift from carbonate‐reef sediments to mangrove peat in the 13th century AD was attended by an input of allogenic (mineral) elements, including mercury. A THg concentration peak (0.8 μg·g −1 ) in brackish pool sediment is 210 Pb‐dated to 1960–1970 AD, but the incorporation of mercury in multiple cores adjacent to the site shows increasing mercury inputs to have occurred before, during Classic‐period Maya occupation and following the sites abandonment. Analysis of element values from site‐scale soil sampling, combined with results from off‐site cores, provides a numerical framework upon which outlier values of THg and other element spatial patterns can be assessed, especially the spatial co‐association of elements related to differences in soil–sediment matrices. Geochemical results from active soils developing from occupation deposits (anthrosols) and sediment cores open up questions concerning contemporary and past mercury accumulation at coastal Mayan sites, and the wider interaction of human and natural biogeochemical processes that occur in human‐modified soils and coastal wetland sediments.